Dynamic Analysis Correlation Of Standard Penetration Resistances With The Adhesion Of Very Stiff To Hard Clays On Driven Piles - Chris D. Thompson (Deep Foundations Institute, 2002)
In Southern Ontario, Canada, piles are frequently driven through competent clayey soils to obtain end bearing on extremely dense till or bedrock. One reason for this is the difficulty at assessing the adhesion of the clayey soils. This is illustrated by texts, such as the Canadian Foundation Engineering Manual, which is the standard of practice in Canada, that indicate that theoretical analysis of the adhesion values of such soils are unreliable. In this paper, the results of high strain dynamic testing have been used to estimate the shaft resistance of 11 closed end pipe piles driven in overconsolidated very stiff to hard clayey tills at four sites by means of the CAPWAP wave equation analysis. More than twenty-five years of experience with bearing capacity predictions by such means have developed considerable confidence in its accuracy. The results were found to correlate reasonably with the average Standard Penetration Resistances of the clays at the sites. There was a linear relationship between an adhesion of 64 kPa at 20 blows per 300 mm and 192 kPa at 60 blows per 300 mm. At one site, 6 piles were tested and found to have a wide range of Standard Penetration Resistance and estimated adhesion in the same stratum. While there was significant scatter of the results, piles would have been safe at design loads obtained from the relationships established by the analysis carried out for this paper after applying appropriate factors of safety.